Incentives for food waste diversion: Exploration of a long term successful Chinese city residential scheme. (10th July 2017) - Li, C.J.; Huang, Y.Y.; Harder, M.K.
Abstract: There are no academic studies of incentives schemes for household recycling which are successful or useful on large scales in the longer term. For food waste sorting very few successful schemes have been reported, with or without incentives. Here the authors report findings about a two-year old, 23, 000-household scheme in Nanjing, China, from an exploratory case study designed to identify key factors using observations, measurements, company data and interviews. Results indicate that residents were initially motivated by the incentives (e.g. points exchanged for eggs) and social influences, but habit was the key factor for maintaining their behaviour, and cited as the main reason they would continue if the incentives stopped. Interestingly, a perceived improvement in the community site's cleanliness was also cited as an ongoing motivation, and social influences was not mentioned. The perceived success of the scheme was confirmed via measurements of participation rates (32%), the weight of food waste diverted (0.62 kg per household), and estimates of the contamination rate (<1%) and food capture rate (30%) 22 months after start. This work identifies key factors for further studies of positive incentives as habit (and thus duration), site cleanliness, and variation in ranking with time of social norms. Highlights: A rare case: successful, large, incentivised, residential food waste diversion scheme. Social norms were nearly as significant as incentives, at the start of the scheme. Most participants expected to continue even if incentives ended, because of habit. Habit was cited as the main reason participants might continue if incentives stopped. Improved site cleanliness (perceived, not seen) was a key motivator for continuing.